Reflections on one dimensional transmission - Klaiman, Shachar (Chemical physics, 2017)
The transmission spectrum of one dimensional potentials is analyzed using the poles of the scattering matrix. Specifically, we derive n-tuple resonance profile formulas that can be used to fit various features in the transmission spectrum. We show in detail the use of the single-resonance profile and the double-resonance profile and their advantage over other commonly used resonance profiles. General aspects of the n-tuple resonance profiles are also discussed.
Available online 15 September 2016
Gesehen am 22.10.2018